ISOLASI, IDENTIFIKASI DAN PEMURNIAN CENDAWAN MIKORIZA ARBUSKULAR (CMA) DARI TANAH BEKAS TAMBANG BATU BARA (Isolation, Identification and Purification of Arbuscular Mycorrhiza Fungi (AMF) from Coal Post Mining Soil) - Elis Kartika; . Lizawati; . Hamzah (Bioplantae, 2012)
Land of coal post-mining is the critical area that generally can not becultivated due to very low levels of fertility of the land, so this landbecomes slighted. One of the alternatives to overcome this problem isthrough inoculation with Arbuscular Mycorrhiza Fungi (AMF).Indigenous AMF (from coal post-mining location) is more potential AMFdeveloping in that area. Therefore, isolation, identification and purificationsteps of AMF spores are required. The objective of this study was toisolate, identify, and purify of arbuscular mycorrhiza fungi from coal postmining area. The study had identified that at this soil was found 3 AMFgenuses, i.e. Glomus, Acaulospora, and Gigaspora. On coal post-miningsoil was found 20 strains of AMF (13 strains of Glomus, 3 strains ofAcaulospora, and 1 strain of Gigaspora). In this soil was dominated byGlomus. Strain’s AMF that was successful isolated from single sporeculture was 4 strains i.e. Glomus sp-3, Glomus sp-6, Glomus sp-15, danGlomus sp-16.